2009
DOI: 10.1111/j.1365-2184.2009.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen environment on mesenchymal stem cell expansion and chondrogenic differentiation

Abstract: Our approach provides new insights into organization of MSC populations in vitro. The results suggest that MSC differentiation is largely reversible and that lineage plasticity is restricted to stem cells and early progenitors. The model predicts a significant impact of short-term low oxygen treatment on MSC differentiation and optimal chondrogenic differentiation at 10-11% pO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 48 publications
5
64
0
2
Order By: Relevance
“…The cells were cultured up to a density A positive effect of hypoxic conditions on the proliferation rate and maintenance of the undifferentiated state was described in several publications [9][10][11][12][13]. Additionally it could be shown that mesenchymal stem cells, which had been cultured under hypoxic conditions (2 -5% oxygen in the aeration gas) showed a better differentiation potential when transferred to normoxic conditions [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were cultured up to a density A positive effect of hypoxic conditions on the proliferation rate and maintenance of the undifferentiated state was described in several publications [9][10][11][12][13]. Additionally it could be shown that mesenchymal stem cells, which had been cultured under hypoxic conditions (2 -5% oxygen in the aeration gas) showed a better differentiation potential when transferred to normoxic conditions [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced proliferation has previously been reported for MSCs maintained at a low oxygen tension. [57][58][59][60] This proliferative potential during monolayer expansion was maintained during chondrogenic differentiation, both in pellet culture, but also in hydrogel culture once FPSCs were stimulated with serum. FPSCs did not appear to proliferate within the hydrogel, but rather on the construct surface.…”
Section: Discussionmentioning
confidence: 99%
“…Within the niche of many adult stem cells, oxygen levels are usually much lower than those in the ambient air or even in the host tissue (Simon and Keith, 2008;Simsek et al, 2010). For instance, oxygen levels in the niches of mesenchymal, hematopoietic and neural stem cells are 2-8%, 1-6% and 1-8%, respectively (Clarke and van der Kooy, 2009;Eliasson and Jonsson, 2010;Krinner et al, 2009;Mohyeldin et al, 2010). Low oxygen tension (hypoxia) is critical for multiple stem cells to maintain their stemness and the hypoxia niche plays a crucial role in the self-renewal and proliferation of the resident stem cells.…”
Section: Introductionmentioning
confidence: 99%